Geochemistry and Genesis of the Hongguleleng Manto-type Cu Deposit, West Junggar, Xinjiang, China: A Recent Study - Jinheng Sun; Ping Shen; Hongdi Pan; Changhao Li; Ge Ma; Wenguang Li (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
The Hongguleleng Cu deposit, located in the east area of West Junggar, Xinjiang, China, is a Manto-type deposit in the Central Asian Orogenic Belt. It presents some differences with other Manto-type Cu deposit. In this paper, we aim to uncover geological difference and discuss genesis with geochemical method. It is hosted by the Middle Ordovician volcano-sedimentary sequence, particularly porous units. The orebodies of this Manto-type deposit are specifically hosted in basalt, andesite, and andesitic breccia host rocks (the particular volcano-sedimentary sequence). Normal faults control the occurrence of these orebodies. The most common minerals in the Hongguleleng deposit are chalcopyrite, pyrite, calcite, chlorite, and epidote. There are three alternation belts and six ore-related stages that have been identified. The epidote-chalcopyrite stage, quartz-calcite-chalcopyrite stage, and chlorite stage are ore forming stage. The \(δ\)34S of chalcopyrite in ore depositing stage varies from 0.94‰ to 2.59‰, indicating that the origin of sulfur is either magma or host volcanic rock. Further, the 206Pb/204Pb, 207Pb/204Pb, and 208Pb/204Pb values of the chlorite-chalcopyrite and quartz-calcite-chalcopyrite stages exist in the range of 17.443–17.847 and 17.855–17.973; 15.472–15.495 and 15.493–15.62; and 37.616–37.666 and 37.689–38.114, respectively, indicating that the metal originates from the Middle Ocean Ridge Basalt (MORB). The \(δ\)13CPDB value of calcite for the epidote-chalcopyrite stage ores, quartz-calcite-chalcopyrite ores with veinlet characteristics, quartz-calcite-chalcopyrite ores with brecciated characteristics, and chlorite-chalcopyrite ores range from -1.4 to -1.5‰, -2.01 to 0.41‰, -1.15 to 0.75‰, and -0.8 to 1.58‰, respectively, while the 18OSMOW ranges from 8.94–10.42‰, 11.83–13.17‰, 13.59–14.04‰, and 12.34–14.18‰, respectively. The C-O isotope of calcite from the Hongguleleng deposit indicates that seawater is an important fluid in ore formation and that modified seawater interacts extensively with the host rock. The presence of hydrothermal magnetite in the quartz-magnetite stage and chlorite in the ore forming stages suggests that temperature decreases from the early to late stages. High Zn and Pb concentrations in pyrite over four stages, with relatively stable contents, indicate that the Zn and Pb content in fluid is also high. The concentration of Cu in the Hongguleleng deposit’s four stages of pyrite follows a decreasing trend, indicating that the concentration of Cu in the ore forming fluid decreases from early to late stage. We argue that this deposit is a Manto-type deposit with modified seawater driving forces based on the information presented above. Keywords: West Junggar The Hongguleleng Manto-type Cu deposit C-O isotope S-Pb isotope Magnetite, chlorite, and pyrite electron microprobe analysis Ore genesis.